Gorgias or on Ideology - Arduini, Stefano (2004)
For the study of Rhetorics as a criticism of ideology, it proves useful to take a look at sofist Gorgias, standpoint on the issue. He separated shared knowledge from common sense and stated that there is no absolute truth because sensorial impressions are not the same for different individuals in different contexts.